A case of COVID-19 with papulovesicular rash that progressed to retiform purpura, accompanied by cherry angiomas - Agirgol, Senay; Çaytemel, Ceyda; Kolan, Ahmet Şah; Vural, Hüseyin (São Paulo Medical Journal, 2021)
CONTEXT: Various skin manifestations have been reported in coronavirus disease. It may be difficult to determine the etiology ofthese lesions in view of the increased frequency of handwashing during the pandemic, along with occurrences of irritant contact dermatitis and allergic contact dermatitis due to disinfectant use; usage of herbal medicine and supplements to strengthen the immune system; and urticarial or maculopapular drug eruptions due to COVID-19 treatment. The variety of associated skin manifestations seen with COVID-19 makes it challenging to identify virus-specific skin manifestations. Petechiae, purpura, acrocyanosis and necrotic and non-necrotic purpura, which can be considered as manifestations of vascular involvement on the skin, have been reported. CASE REPORT: Here, we report a case of eruptive cherry angiomas, which was thought to have developed due to COVID-19, with a papulovesicular rash on distal extremities that progressed over time to reticular purpura. CONCLUSION: The case presented had a papulovesicular rash at the onset, which evolved to retiform purpura, and eruptive cherry angiomas were observed. It should be kept in mind that dermatological signs may vary in patients with COVID-19.